Assessment of the work ability related factors in diabetic patients - Behrang Motamed; Aisan Mosafer; Mirsaeed Attarchi (Heliyon, 2022)
Diabetes is a common disease all around the world. Diabetes can reduce work and job restrictions. The aim of this study was to assessment of work ability (WA) related factors in diabetic patients. All demographic, occupational, and clinical information of 176 diabetic patients who were referred to the Razi hospital Rasht, Iran, in 2021 was collected. Also, the WA questionnaire for patients with a score from 7 to 49 was completed. The mean score of WA in patients was 28.8. 46.6%, 28.4%, 22.2%, and 2.8% of patients had weak, moderate, good, and excellent WA, respectively. There was a significant association between age, body mass index (BMI), marital status, education, habitat, health insurance status, type of job, job satisfaction status, work shift, underlying disease, history of diabetes, complications of diabetes, fasting blood sugar (FBS), hemoglobin A1c (HbA1C), and WA of patients (P < 0.05). Analysis showed that the variables of job satisfaction and the presence of diabetes complications were significantly associated with the WA. Nearly half of the diabetic patients had weak WA, in which demographic, occupational, and diabetes related factors were associated with weak WA.